Biotechnology & genetic engineering reviews. - Harding, S. E. (Stephen E.); Tombs, M. P. (Biotechnology & Genetic Engineering Reviews., 2008)
Containing more than a dozen original, major review articles from authors published in leading journals and covering important developments in industrial, agricultural, and medical applications of biotechnology, this newest edition from the well-established hardcover review series focuses primarily on the genetic manipulation of organisms. Covering issues ranging from gene expression and genetic regulations to plant bioreactors and enzymatic processing, this reference will benefit students in the fields of biochemistry, genetics, molecular biology, and pharmaceutical sciences.